2023
DOI: 10.1155/2023/9034073
|View full text |Cite
|
Sign up to set email alerts
|

Work Engagement and Safety Behavior of Nurses in Specialized Cancer Hospitals: The Mediating Role of Self-Efficacy

Abstract: Aim. This paper aimed to examine the current state of nurse safety behavior, and the effect of work engagement on it, and to explore the mediating effect of self-efficacy between work engagement and nurse safety behavior in specialized cancer hospitals. Background. Nurse safety behavior affects the quality of care and outcomes for patients with cancer. The research proves that self-efficacy is associated with work engagement, but the relationship between self-efficacy, work engagement, and nurse safety behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…This performance can be modulated by both personal and work-related factors, such as depression and professional self-efficacy. This underlines the need to investigate and promote safe behaviors that improve the quality of care ( 53 ). On the other hand, it has been shown that high job performance, along with job satisfaction and organizational commitment, can have a positive impact on nurses' performance and on the quality of care provided to patients ( 54 ).…”
Section: Introductionmentioning
confidence: 99%
“…This performance can be modulated by both personal and work-related factors, such as depression and professional self-efficacy. This underlines the need to investigate and promote safe behaviors that improve the quality of care ( 53 ). On the other hand, it has been shown that high job performance, along with job satisfaction and organizational commitment, can have a positive impact on nurses' performance and on the quality of care provided to patients ( 54 ).…”
Section: Introductionmentioning
confidence: 99%